International capital flows in Finland 1975-1990: The role of expectations - Arto Kovanen (Bank of Finland, 1992)
Financial markets in Finland have undergone important structural changes over the 1980's. Most important have been the emergence of a wellfunctioning short-term money markets and the relaxation of most of the foreign exchange controls. These elements have created a situation where the economy is increasingly dependent on the developments in the rest of the world. The present study may be viewed as an extension to Hämäläinen and Kovanen (1991). The purpose is to examine how income and exchange rate expectations influence the determination of intemational capital flows. Theoretical foundations are supported by empirical evidence. Exchange rate expectations have a statistically significant role to play in the adjustment process, in particular during the final years of 1980's. Also income expectations are important for the adjustment of the demand for money. A somewhat less important, but nevertheless interesting, result concems the possibility of short-run overshooting in the net capital flows in response to changes in domestic credit. in the short runo
URN:NBN:fi:bof-201808021843
Keywords: 330